Total Cost of Ownership along the Mine Asset Management and Supply Chain - Noorbakhsh, Amir (Curtin University, 2019)
Mining industry uses Total Cost of Ownership (TCO) to improve and extend the procurement decision beyond the initial price to consider all costs over the lifecycle of assets. Along with TCO implementation, the risk of supply also needs to be evaluated. The findings of this study provides mining firms with motivation and methods to develop and utilize strategies for monitoring and mitigating the cost of TCO implementation over the entire asset life cycle.